2018
DOI: 10.1002/yea.3321
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antagonistic yeasts for biocontrol applications on apples or in soil by quantitative analyses of synthetic yeast communities

Abstract: Antagonistic yeasts suppress plant pathogenic fungi by various mechanisms, but their biocontrol efficacy also depends on the ability to compete and persist in the environment. The goal of the work presented here was to quantify the composition of synthetic yeast communities in order to determine the competitiveness of different species and identify promising candidates for plant protection. For this purpose, colony counting of distinct species and matrix‐assisted laser desorption ionization time‐of‐flight mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…The yeast Metschnikowia pulcherrima is globally distributed and frequently isolated from the phyllosphere; in particular from flowers and fruits (Slavikova et al , ; Pelliccia et al , ; Vadkertiova et al , ). Competition assays of 40 yeasts against a diverse set of 16 filamentous fungi identified M. pulcherrima as the overall strongest antagonist (Hilber‐Bodmer et al , ) and the same isolate was highly competitive against other antifungal yeasts on apples (Gross et al , ). The species exhibits strong antagonistic activity against apple postharvest diseases caused by Alternaria , Aspergillus , Botrytis, Fusarium, Monilinia and Penicillium species (Piano et al , ; Janisiewicz et al , ; Spadaro et al , ; Saravanakumar et al , ; Turkel et al , ; Ruiz‐Moyano et al , ) and was also identified as a potential biocontrol organism against foodborne pathogens of freshly cut apples (Leverentz et al , ) as well as fungal grape diseases (De Curtis et al , ; Parafati et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The yeast Metschnikowia pulcherrima is globally distributed and frequently isolated from the phyllosphere; in particular from flowers and fruits (Slavikova et al , ; Pelliccia et al , ; Vadkertiova et al , ). Competition assays of 40 yeasts against a diverse set of 16 filamentous fungi identified M. pulcherrima as the overall strongest antagonist (Hilber‐Bodmer et al , ) and the same isolate was highly competitive against other antifungal yeasts on apples (Gross et al , ). The species exhibits strong antagonistic activity against apple postharvest diseases caused by Alternaria , Aspergillus , Botrytis, Fusarium, Monilinia and Penicillium species (Piano et al , ; Janisiewicz et al , ; Spadaro et al , ; Saravanakumar et al , ; Turkel et al , ; Ruiz‐Moyano et al , ) and was also identified as a potential biocontrol organism against foodborne pathogens of freshly cut apples (Leverentz et al , ) as well as fungal grape diseases (De Curtis et al , ; Parafati et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The species A. pullulans and the A. pullulans strain NBB 7.2.1 are strongly antagonistic against several plant pathogens and highly competitive against other yeasts on apple fruits [9,37,38]. Here, A. pullulans NBB 7.2.1 exhibited comparable growth and antagonistic activity as A. pullulans EXF-150, but inhibited F. oxysporum NRRL 26381/CL57 more strongly than A. melanogenum CBS 110374, A. namibiae CBS 147.97, and A. subglaciale EXF-2481 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, many have not yet been explored as potential biocontrol agents against fruit-spoilage organisms. Similarly, P. kluyveri has also been determined as an antagonistic yeast for biocontrol applications [44,45].…”
Section: Introductionmentioning
confidence: 99%